(untitled) (Revista INTEREDU11, 2022)
This research has been driven by an ongoing qualitative study which has focused on preschool education in order to describe those emerging educational contexts in the school environment, whenever the cultural, social intelligence and daily epistemology of children set students outside the prescriptive framework for education, and so, they finally find their place in an unfinished and unclear curriculum for this level. Both the observation and the ethnographic records applied in this study have allowed us to amplify both, the listening and the look of this blind spot, providing a description of the place where the students’ own culture coexist, and so, their feelings, emotions, intuition and connotative perception, as well as those other elements that together with children give true meaning to pedagogy. This research invites other researchers to consider this document as a source of relevant information, as it can contribute to the improvement of education.